2022
DOI: 10.1002/cpdd.1045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hepatic Impairment on the Pharmacokinetic Profile and Safety of Lobeglitazone

Abstract: In this open‐label, single‐dose, parallel‐group study, we compared the pharmacokinetic profile and safety of lobeglitazone, a thiazolidinedione acting as an agonist for peroxisome proliferator‐activated receptors, in patients with hepatic impairment (HI) and healthy matched controls for age, sex, and body weight. After a single oral dose of lobeglitazone (0.5 mg), the lobeglitazone (parent drug) and M7 (major metabolite) plasma concentrations and pharmacokinetic parameters were analyzed and compared between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The pharmacokinetic profile and safety of lobeglitazone were studied on T2DM patients with hepatic impairment compared with control groups. It was found that lobeglitazone can be safely prescribed to patients for T2DM with mild or moderate hepatic impairment without dose adjustment [23]. Generally, TZDs are related to various safety concerns such as weight gain.…”
Section: Safety Pharmacologymentioning
confidence: 99%
“…The pharmacokinetic profile and safety of lobeglitazone were studied on T2DM patients with hepatic impairment compared with control groups. It was found that lobeglitazone can be safely prescribed to patients for T2DM with mild or moderate hepatic impairment without dose adjustment [23]. Generally, TZDs are related to various safety concerns such as weight gain.…”
Section: Safety Pharmacologymentioning
confidence: 99%